ANALISIS BUDAYA KERJA TENAGA KEPENDIDIKAN BIRO UMUM DAN KEUANGAN UNIVERSITAS TADULAKO - Prihatin, Henny (Katalogis, 2017)
This study aimed to analyze the work culture of education personnel at Tadulako University Bureau of Public Administration and Finance. The research method is qualitative research, with the informants as much as 7 (seven) respondent, selected using purposive sampling. Data were collected using the methods of observation, interviews, and documentation. The results explained that the work culture of education personnel at Tadulako University Bureau of Public Administration and Finance had not been running optimally because from the 5 aspects studied, (1) the honesty aspect had not been running optimally because there were still many employees providing work result reports which were not in accordance with the facts on the ground; 2) the perseverance aspect had not been running optimally because there were still many employees neglecting work times so that the work did not achieve the target; 3) the aspect of creativity in performing the duties can be said had not been maximized, because there were still many divisions that make the same programs with the previous years without any change in the direction of progress. This was due to lack of coordination and supervision from the elements of leadership. 4) The discipline aspect had not been running optimally because there were still employees who did not appreciate the time; and 5) the responsibility aspect had not been running optimally because there are still employees who only worked after the leadership’s orders, personnel transfer was one of the factors resulting in weak responsibility from education personnel at Tadulako University Bureau of Public Administration and Finance.